UJI EFEKTIVITAS EKSTRAK ETANOL KULIT PISANG MAS (Musa acuminata Colla) TERHADAP PENURUNAN KADAR KOLESTEROL TIKUS (Rattus norvegicus) HIPERLIPIDEMIA - Sukmawati, Sukmawati; Wati, Aulia; Meilinda, Mega; Asmaliani, Ira (Jurnal Ilmiah As-Syifaa, 2020)
Hyperlipidemia is the escalation level of cholesterol and triglyceride in blood. Lady finger banana peel had chemical flavonoid, tanin, and saponin contents having the activity to reduce cholesterol level. The research aimed to determine the effect of cholesterol level reduction of ethanol exctract of lady finger peel on hyperlipidemia rat. The research used twenty rats divided into five groups. Group I (negative control) was given Na. CMC of 1% b/v, group II (positive control) was given simvastatin of 1,023 mg/kgBW, group III, IV, V groups were given the extract of 500 mg/kgBW 1000 mg/kgBW, and 1500 mg/kgBW. The rats were fed a high dietary fat during treatment and induces with pristine cholesterol for twenty one days. The measurement of rat cholesterol level was conducted on day 0, 22 and 36. The result were statistically processed using One Way Anova proceeded to Post Hoc Bonferroni. The result of the research showed that the positive control group had no different tangible effect to ethanol extract of lady finger banana groups (p>0,5). In conclusion, the ethanol extract of lady finger banana had the activity in reducing cholesterol level with effective doses of 500 mg/kgBW, 1000 mg/kgBW, and 1500 mg/kgBW.